Analisis Pengendalian Persediaan Produk Miyako Menggunakan Metode Analisis ABC pada Toko Ritel Aneka Jaya, Jember - Aldo Pratama (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze inventory control of Miyako products at Aneka Jaya Retail Store in Jember using the ABC Analysis, Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) methods. The main issue faced by the store is the imbalance between stock shortages and overstocking, which affects operational costs and customer service. The ABC method is used to classify products based on annual inventory investment value, EOQ to determine the optimal order quantity, Safety Stock to anticipate demand uncertainty, and ROP to determine the appropriate reorder timing. The results show that product group A accounts for more than 70% of inventory value and requires the highest monitoring priority. EOQ calculations provide efficient order quantities, though limited warehouse capacity presents implementation challenges. The Safety Stock and ROP methods are proven effective in maintaining stock availability and preventing stockouts. By applying these methods, Aneka Jaya can improve inventory management efficiency and significantly reduce operational costs.
FINALISASI oleh Arif 2026 Mei 21
Keywords: Inventory Control; ABC Analysis; EOQ; Safety Stock; Retail Electronics; Reorder Point